Leadership skills development in medical student education: systematic review - Ruiz-Chaves, Warner (2024)
Introduction: The training in leadership skills by the medical student body is a topic increasingly addressed by virtue of the need for this professional to respond to the changing circumstances of their environment, there are different experiences at the research level that are outlined in this manuscript; therefore, it was proposed to analyze the thematic and/or research trends on the development of leadership skills in undergraduate and postgraduate training of the medical person during the years 2018 and 2023 to join this area of knowledge. Background: The systematic review included the electronic databases Scopus, Education Research Complete, PubMed and Web of Science, using the PRISMA methodology, so that they meet a series of indicators for reviews of this type. Discussion: Three thematic and/or research areas were identified: development of leadership skills in students, development of educational programs and projects and, finally, studies by gender.